2009
DOI: 10.1080/13504850701578926
|View full text |Cite
|
Sign up to set email alerts
|

Native-migrant differences in risk attitudes

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 9 publications
9
99
0
1
Order By: Relevance
“…These results may clash with what was previously believed or to what intuition would predict but are in line with previous studies. Bonin et al (2009) [7] confirm that first-generation migrants have lower risk attitudes than natives, which only equalize in the second generation. One explanation could be related to the first generation's insecurities in their social and economic situation in Germany.…”
Section: Risk Behaviorsupporting
confidence: 51%
See 1 more Smart Citation
“…These results may clash with what was previously believed or to what intuition would predict but are in line with previous studies. Bonin et al (2009) [7] confirm that first-generation migrants have lower risk attitudes than natives, which only equalize in the second generation. One explanation could be related to the first generation's insecurities in their social and economic situation in Germany.…”
Section: Risk Behaviorsupporting
confidence: 51%
“…Among these persons with migration background, roughly 68 percent belong to the group of people with their own migration experience (comparable to the first generation immigrants) and 32 percent to the group of persons without migration experience (second or later immigrant generation). 7 Also in the GSOEP data, the majority of the immigrants observed, namely 76.82 percent, are classified 5 hold other than German citizenship, one of the parents is not German born or has a foreign nationality 6 Table 2). This bias from official data might be related to the fact that the GSOEP contains information mostly about individuals who are older than 16 years of age.…”
Section: Immigrant Population In Germanymentioning
confidence: 99%
“…This could occur because migrants may simply be more risk-loving than natives (Sahota 1968). Bonin et al (2009) found the reverse suggesting that selectivity issues and general ethnic differences in risk attitudes may be possible at work: If the receiving country is a welfare state, it may receive more of the risk-averse migrants. Or the more risk-loving migrants may move onward or return home.…”
Section: Literaturementioning
confidence: 95%
“…To date, there is only limited empirical evidence verifying this hypothesis, and such evidence is gathered from either laboratory experiments or data predominantly collected in high income countries with established institutions (Bonin et al, 2009 and2012;Jaeger et al, 2010;Dohmen et al, 2011 and2012;Williams and Baláž, 2014). Evidence from countries undergoing rapid economic and social transformations is minimal (Gibson and McKenzie, 2009;Hao et al, 2014;Dohmen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who are willing to take more risk score high on this variable. The measurement of risk attitudes by means of a single question in large-scale surveys is not uncommon, and examples have appeared in earlier research (Bonin et al 2009;Bönte and Piegeler 2013;Jaeger et al 2010). The usefulness of a general selfassessment of risk by respondents is demonstrated by Dohmen et al (2011, p.524), who conclude that ''(…) responses to the general risk question are a reliable predictor of actual risky behaviour, even controlling for a large number of observables''.…”
Section: Perceived Riskmentioning
confidence: 99%